The determinants of hiring in local labor markets: The role of demand and supply factors - Stefan Eriksson; Karolina Stadin (Uppsala University, Department of Economics, 2011)
This paper studies the determinants of hiring. We use the search-matching model with imperfect competition in the product market from Carlsson, Eriksson and Gottfries (2011) to derive an equation for total hiring in a local labor market, and estimate it on Swedish panel data. When product markets are imperfectly competitive, product demand shocks have a direct effect on employment. Our results show that product demand is important for hiring. Moreover, we show that conventional measures of vacancies do not fully capture the effect of product demand on hiring. Finally, we show that the number of unemployed workers has a positive effect on hiring as predicted by search-matching models.
urn:nbn:se:uu:diva-164691
Keywords: E24; J23; J64; 330; Hiring; Search-matching; Imperfect Competition; Unemployment; Personalbeschaffung; Arbeitsplatzsuchmodell; Unvollkommener Wettbewerb; Schweden